Temperate forests at southern South America: Challenges for management and conservation to face climate change - Martínez Pastur, Guillermo José; Rodríguez‑Souilla, Julián; Barrera, Marcelo Daniel; Toro Manríquez, Mónica D.R.; Huertas Herrera, Alejandro; Peri, Pablo Luis (Elsevier, 2025)
Climate change is a phenomenon that presents significant variations at the planetary, regional, and local scales, but with different magnitudes and directions. The existence of tools based on remote sensing at the landscape level may assist decision-making processes in management and conservation to face climate change. Using these tools, it is possible to identify differential spatial trends in temperature and precipitation during the last decades affecting the ecosystems and net primary productivity. Nowadays, it is possible to quantify the changes that have occurred in natural ecosystems on a small scale, in relation to the current native forest cover, and their interaction with the main socioeconomic factors (e.g., fires events). In this context, it is necessary to rethink about the forestry practices that must be adapted to each region and that must be flexible enough to adapt to a wide range of possible climate and anthropogenic scenarios. The recommendations for the development of new management and conservation strategies must be designed at a regional, provincial, or ranch scale, in relation to the involved ecosystems (e.g., assemblage of species or the main uses by the society). Monitoring must be the base for the new management paradigms, analyzing the change trends and relationships with climate using remote sensor tools. Climate change must be incorporated in the planning for the use and conservation of our native temperate forests of Argentina.